Correlations between moral courage scores and social desirability scores among medical residents and fellows in Argentina - Raúl Alfredo Borracci; Graciana Ciambrone; José María Alvarez Gallesio (Journal of Educational Evaluation for Health Professions, 2020)
Purpose Moral courage refers to the conviction to take action on one’s ethical beliefs despite the risk of adverse consequences. This study aimed to evaluate correlations between social desirability scores and moral courage scores among medical residents and fellows, and to explore gender- and specialty-based differences in moral courage scores. Methods In April 2018, the Moral Courage Scale for Physicians (MCSP), the Professional Moral Courage (PMC) scale and the Marlowe-Crowne scale to measure social desirability were administered to 87 medical residents from Hospital Alemán in Buenos Aires, Argentina. Results The Cronbach α coefficients were 0.78, 0.74, and 0.81 for the Marlowe-Crowne, MCSP, and PMC scales, respectively. Correlation analysis showed that moral courage scores were weakly correlated with social desirability scores, while both moral courage scales were strongly correlated with each other. Physicians who were training in a surgical specialty showed lower moral courage scores than nonsurgical specialty trainees, and men from any specialty tended to have lower moral courage scores than women. Specifically, individuals training in surgical specialties ranked lower on assessments of the “multiple values,” “endurance of threats,” and “going beyond compliance” dimensions of the PMC scale. Men tended to rank lower than women on the “multiple values,” “moral goals,” and “endurance of threats” dimensions. Conclusion There was a poor correlation between 2 validated moral courage scores and social desirability scores among medical residents and fellows in Argentina. Conversely, both moral courage tools showed a close correlation and concordance, suggesting that these scales are reasonably interchangeable.